Improvement of public roads - Parrack, Albert William (My University, 1900)
Introduction: Perhaps no question is of more universal importance, and yet less written or spoken on, than that of public wagon roads. The railroad is a subject of common discussion. It forms a part of the theme of the political orator, is commented on by every citizen who thinks and talks on public questions, and no layman is so ignorant as not to have an opinion about how the railroads, factories and schools should be controlled. This is true of questions relating to taxation, tariff, money, and expansion; but, when it comes to the question of wagon roads, that is a subject too common and insignificant for many to think on; and, although we are constantly worrying over it, the wagon road is left to the care of the wind and flood and a few yearly scratches directed by the inefficient Kansas “Road-boss.” One reason why the development of the common road has been so slow is the marvelous increase in railroad building, it being assumed that the latter obviates, to a considerable extent, the necessity of the former. But, notwithstanding the fact that our whole country is covered with a network of railroads, there is still as great a need of good public roads as before; in fact, this great system of railroads seems to have increased rather than have diminished their necessity. It is true that the farmers do not have to haul their farm products twenty or thirty miles to market, as they did fifty or seventy-five years ago, because the railroad has taken the place of the public roads connecting the farming districts with the central markets, such as Kansas City, St. Louis and Chicago. But, on the other hand, the existence of the railroads effects a more complete utilization of the land of a community, and a large increase in the number of inhabitants. This means an increase in agricultural products, and the necessity of more and better roads that these products may be hauled to the local market—the point at which the farmer now disposes of his produce; though the final market is any place on the globe that is in telegraphic and steam connection with his station, and where there is a demand for what he has to sell.
Citation: Parrack, Albert William. Improvement of public roads. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Infrastructure; Roads; Wagon Roads; Shipping Produce; Transportation; Theses